Fabrication of floor tiles from recycled HDPE bottle filled recycled glass composite using hot press method - Ramily, Nurlina Aimi (2018)
rHDPE tiles are made out of plastics that can be used to cover walls and floors. The purpose of this experiment is to produce rHDPE tiles that are from rHDPE plastic bottles and some portion of Soda Lime Silicate Glass (SLSG) in selected ratio. It is in the interest of this experiment to solve the problems with conventional tiles, which are easily broken and discoloured. rHDPE plastic bottles melted at 140°C for around 4 minutes then the proportion of SLSG powder were poured and the mixed composition were crushed before hot press proses into the designated mould with size (200rnm x 200mm x 5mm).The fabrication of the tile is using Hot Press Method. The estimate time needed for the cooling process is between 5 minutes setup within the hot press machine. These samples go through 2 type of test which are Flexural Test and Impact Test. All the mechanical properties of proportion behaviour recorded in the table and analysis on the new properties were done.